2000
DOI: 10.1097/00001888-200005000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Teaching of Cultural Issues in U.S. and Canadian Medical Schools

Abstract: Most U.S. and Canadian medical schools provide inadequate instruction about cultural issues, especially the specific cultural aspects of large minority groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 3 publications
1
86
0
1
Order By: Relevance
“…In response to the increasing cultural diversity of the population, U.S. medical schools have increased their efforts to include multicultural issues in their curricula. Comparison of studies conducted in 1978 and then in 2000 found a 45% increase (from 60% to 95%) in the integration of socio-cultural issues into the curricula (Flores, Gee, & Kastner, 2000;Wyatt, Bass, & Powell, 1978). Similar studies of U.S. nursing school curricula could not be found, but there has been an increasing number of publications in the nursing literature exploring the content, teaching methods, evaluation and faculty qualifications needed to ensure that nursing programs adequately prepares nurses to meet the needs of culturally diverse patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the increasing cultural diversity of the population, U.S. medical schools have increased their efforts to include multicultural issues in their curricula. Comparison of studies conducted in 1978 and then in 2000 found a 45% increase (from 60% to 95%) in the integration of socio-cultural issues into the curricula (Flores, Gee, & Kastner, 2000;Wyatt, Bass, & Powell, 1978). Similar studies of U.S. nursing school curricula could not be found, but there has been an increasing number of publications in the nursing literature exploring the content, teaching methods, evaluation and faculty qualifications needed to ensure that nursing programs adequately prepares nurses to meet the needs of culturally diverse patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Non-concordance of staff was associated with more perceived disrespect, indicating that cultural sensitivity training may be needed for all health care staff members. Physician cultural competency training can occur in medical school and in specialized training programs after graduation, [25][26][27] but ancillary staff may not receive opportunities to learn cultural competency during employment training, so the responsibility for training may rest with individual institutions. An important component of cultural competency is the availability of adequate interpreter services, and studies have demonstrated that interpreter services improve patient-provider communication.…”
Section: Discussionmentioning
confidence: 99%
“…Previous surveys documented that the inclusion of cultural diversity education and training in Canadian undergraduate medical curricula was inadequate with 67% (11 out of 16) Canadian medical schools incorporating some aspect of multicultural issues 29 , 37 . They recommended the development of increased educational opportunities to equip students with knowledge about cultural health beliefs and health problems of diverse cultural groups, and provide them with crosscultural communication skills.…”
Section: Canadamentioning
confidence: 99%